Treatment for Posttraumatic Stress Disorder in Military and Veteran Populations: Initial Assessment - Institute of Medicine (The National Academies Press, 2012)
Prior to the military conflicts in Iraq and Afghanistan, wars and conflicts have been characterized by such injuries as infectious diseases and catastrophic gunshot wounds. However, the signature injuries sustained by United States military personnel in these most recent conflicts are blast wounds and the psychiatric consequences to combat, particularly posttraumatic stress disorder (PTSD), which affects an estimated 13 to 20 percent of U.S. service members who have fought in Iraq or Afghanistan since 2001. PTSD is triggered by a specific traumatic event - including combat - which leads to symptoms such as persistent re-experiencing of the event; emotional numbing or avoidance of thoughts, feelings, conversations, or places associated with the trauma; and hyperarousal, such as exaggerated startle responses or difficulty concentrating. As the U.S. reduces its military involvement in the Middle East, the Departments of Defense (DoD) and Veterans Affairs (VA) anticipate that increasing numbers of returning veterans will need PTSD services. As a result, Congress asked the DoD, in consultation with the VA, to sponsor an IOM study to assess both departments' PTSD treatment programs and services. Treatment for Posttraumatic Stress Disorder in Military and Veteran Populations: Initial Assessment is the first of two mandated reports examines some of the available programs to prevent, diagnose, treat, and rehabilitate those who have PTSD and encourages further research that can help to improve PTSD care.

Social and Economic Costs of Violence: Workshop Summary - Institute of Medicine; National Research Council (The National Academies Press, 2012)
Measuring the social and economic costs of violence can be difficult, and most estimates only consider direct economic effects, such as productivity loss or the use of health care services. Communities and societies feel the effects of violence through loss of social cohesion, financial divestment, and the increased burden on the healthcare and justice systems. Initial estimates show that early violence prevention intervention has economic benefits. The IOM Forum on Global Violence Prevention held a workshop to examine the successes and challenges of calculating direct and indirect costs of violence, as well as the potential cost-effectiveness of intervention.

Aging in Asia: Findings from New and Emerging Data Initiatives - National Research Council (The National Academies Press, 2012)
The population of Asia is growing both larger and older. Demographically the most important continent on the world, Asia's population, currently estimated to be 4.2 billion, is expected to increase to about 5.9 billion by 2050. Rapid declines in fertility, together with rising life expectancy, are altering the age structure of the population so that in 2050, for the first time in history, there will be roughly as many people in Asia over the age of 65 as under the age of 15. It is against this backdrop that the Division of Behavioral and Social Research at the U.S. National Institute on Aging (NIA) asked the National Research Council (NRC), through the Committee on Population, to undertake a project on advancing behavioral and social research on aging in Asia. Aging in Asia: Findings from New and Emerging Data Initiatives is a peer-reviewed collection of papers from China, India, Indonesia, Japan, and Thailand that were presented at two conferences organized in conjunction with the Chinese Academy of Sciences, Indian National Science Academy, Indonesian Academy of Sciences, and Science Council of Japan; the first conference was hosted by the Chinese Academy of Social Sciences in Beijing, and the second conference was hosted by the Indian National Science Academy in New Delhi. The papers in the volume highlight the contributions from new and emerging data initiatives in the region and cover subject areas such as economic growth, labor markets, and consumption; family roles and responsibilities; and labor markets and consumption.

Communications and Technology for Violence Prevention: Workshop Summary - Institute of Medicine; National Research Council
In the last 25 years, a major shift has occurred in the field of violence prevention, from the assumption that violence is inevitable to the realization that violence is preventable. As we learn more about what works to reduce violence, the challenge facing those who work in the field is how to use all of this new information to rapidly deploy or enhance new programs. At the same time, new communications technologies and distribution channels have altered traditional means of communications, and have made community-based efforts to prevent violence possible by making information readily available. How can these new technologies be successfully applied to the field of violence prevention? On December 8-9, 2011, the IOM's Forum on Global Violence Prevention held a workshop to explore the intersection of violence prevention and information and communications technology. The workshop - called \

The Mental Health and Substance Use Workforce for Older Adults: In Whose Hands? - Institute of Medicine (The National Academies Press, 2012)
At least 5.6 million to 8 million2014nearly one in five2014older adults in America have one or more mental health and substance use conditions, which present unique challenges for their care. With the number of adults age 65 and older projected to soar from 40.3 million in 2010 to 72.1 million by 2030, the aging of America holds profound consequences for the nation. For decades, policymakers have been warned that the nation's health care workforce is ill-equipped to care for a rapidly growing and increasingly diverse population. In the specific disciplines of mental health and substance use, there have been similar warnings about serious workforce shortages, insufficient workforce diversity, and lack of basic competence and core knowledge in key areas. Following its 2008 report highlighting the urgency of expanding and strengthening the geriatric health care workforce, the IOM was asked by the Department of Health and Human Services to undertake a complementary study on the geriatric mental health and substance use workforce. The Mental Health and Substance Use Workforce for Older Adults: In Whose Hands? assesses the needs of this population and the workforce that serves it. The breadth and magnitude of inadequate workforce training and personnel shortages have grown to such proportions, says the committee, that no single approach, nor a few isolated changes in disparate federal agencies or programs, can adequately address the issue. Overcoming these challenges will require focused and coordinated action by all.

Synthesis of Information Related to Transit Problems: 2012 - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2012)
TRB2019s Transit Cooperative Research Program (TCRP) Research Results Digest 104: Synthesis of Information Related to Transit Problems is a digest of the progress and status of TCRP Project J-7, 201cSynthesis of Information Related to Transit Problems,201d for which the Transportation Research Board is the agency conducting the research.

Child Maltreatment Research, Policy, and Practice for the Next Decade: Workshop Summary - Institute of Medicine; National Research Council
In 1993 the National Research Council released its landmark report Understanding Child Abuse and Neglect (NRC, 1993). That report identified child maltreatment as a devastating social problem in American society. Nearly 20 years later, on January 30-31, 2012, the Institute of Medicine (IOM) and NRC's Board on Children, Youth and Families help a workshop, Child Maltreatment Research, Policy, and Practice for the Next Generation, to review the accomplishments of the past two decades of research related to child maltreatment and the remaining gaps. \

Role of Human Factors in Preventing Cargo Tank Truck Rollovers - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2012)
TRB2019s Hazardous Materials Cooperative Research Program (HMCRP) Report 7: Role of Human Factors in Preventing Cargo Tank Truck Rollovers analyzes the causes of the major driver factors contributing to cargo tank truck rollovers and offers safety, management, and communication practices that can be used to help potentially minimize or eliminate driver errors in cargo tank truck operations.The report focuses on three areas of practice–rollover-specific driver training and safety programs, the use of behavior management techniques, and the use of fitness-for-duty management practices–that could have long-lasting benefits for motor carriers of all sizes across the tank truck industry.

Application of Lightweighting Technology to Military Aircraft, Vessels, and Vehicles - National Research Council
Lightweighting is a concept well known to structural designers and engineers in all applications areas, from laptops to bicycles to automobiles to buildings and airplanes. Reducing the weight of structures can provide many advantages, including increased energy efficiency, better design, improved usability, and better coupling with new, multifunctional features. While lightweighting is a challenge in commercial structures, the special demands of military vehicles for survivability, maneuverability and transportability significantly stress the already complex process. Application of Lightweighting Technology to Military Vehicles, Vessels, and Aircraft assesses the current state of lightweighting implementation in land, sea, and air vehicles and recommends ways to improve the use of lightweight materials and solutions. This book considers both lightweight materials and lightweight design; the availability of lightweight materials from domestic manufacturers; and the performance of lightweight materials and their manufacturing technologies. It also considers the \

Epilepsy Across the Spectrum: Promoting Health and Understanding - Institute of Medicine (The National Academies Press, 2012)
Although epilepsy is one of the nation's most common neurological disorders, public understanding of it is limited. Many people do not know the causes of epilepsy or what they should do if they see someone having a seizure. Epilepsy is a complex spectrum of disorders that affects an estimated 2.2 million Americans in a variety of ways, and is characterized by unpredictable seizures that differ in type, cause, and severity. Yet living with epilepsy is about much more than just seizures; the disorder is often defined in practical terms, such as challenges in school, uncertainties about social situations and employment, limitations on driving, and questions about independent living. The Institute of Medicine was asked to examine the public health dimensions of the epilepsies, focusing on public health surveillance and data collection; population and public health research; health policy, health care, and human services; and education for people with the disorder and their families, health care providers, and the public. In Epilepsy Across the Spectrum, the IOM makes recommendations ranging from the expansion of collaborative epilepsy surveillance efforts, to the coordination of public awareness efforts, to the engagement of people with epilepsy and their families in education, dissemination, and advocacy for improved care and services. Taking action across multiple dimensions will improve the lives of people with epilepsy and their families. The realistic, feasible, and action-oriented recommendations in this report can help enable short- and long-term improvements for people with epilepsy. For all epilepsy organizations and advocates, local, state, and federal agencies, researchers, health care professionals, people with epilepsy, as well as the public, Epilepsy Across the Spectrum is an essential resource.

A Review of NASA Human Research Program's Scientific Merit Assessment Processes: Letter Report - Institute of Medicine (The National Academies Press, 2012)
At the request of NASA, an IOM committee reviewed NASA Human Research Program's (HRP's) Scientific Merit Assessment Processes for directed research. Directed research is commissioned or noncompetitively awarded research that is not competitively solicited because of specific reasons, such as time limitations or highly focused or constrained research topics. The scientific merit assessment processes have been developed by NASA to evaluate individual directed research tasks in order to ensure the scientific integrity of the HRP's directed research portfolio. The committee examined the HRP's current scientific merit assessment processes and conducted a public workshop to identify best practices among other federal agencies that use various assessment processes for similar types of directed research. Review of NASA Human Research Program's Scientific Merit Processes: Letter Report finds that the scientific merit assessment process used by the HRP for directed research is scientifically rigorous and is similar to the processes and merit criteria used by many other federal agencies and organizations - including the Department of Defense, National Institutes of Health, and the United States Department of Agriculture - for comparable types of research. This report also makes recommendations on ways to streamline and bolster the accountability and transparency of NASA's current processes.

Small Populations, Large Effects: Improving the Measurement of the Group Quarters Population in the American Community Survey - National Research Council (The National Academies Press, 2012)
In the early 1990s, the Census Bureau proposed a program of continuous measurement as a possible alternative to the gathering of detailed social, economic, and housing data from a sample of the U.S. population as part of the decennial census. The American Community Survey (ACS) became a reality in 2005, and has included group quarters (GQ)-such places as correctional facilities for adults, student housing, nursing facilities, inpatient hospice facilities, and military barracks-since 2006, primarily to more closely replicate the design and data products of the census long-form sample. The decision to include group quarters in the ACS enables the Census Bureau to provide a comprehensive benchmark of the total U.S. population (not just those living in households). However, the fact that the ACS must rely on a sample of what is a small and very diverse population, combined with limited funding available for survey operations, makes the ACS GQ sampling, data collection, weighting, and estimation procedures more complex and the estimates more susceptible to problems stemming from these limitations. The concerns are magnified in small areas, particularly in terms of detrimental effects on the total population estimates produced for small areas. Small Populations, Large Effects provides an in-depth review of the statistical methodology for measuring the GQ population in the ACS. This report addresses difficulties associated with measuring the GQ population and the rationale for including GQs in the ACS. Considering user needs for ACS data and of operational feasibility and compatibility with the treatment of the household population in the ACS, the report recommends alternatives to the survey design and other methodological features that can make the ACS more useful for users of small-area data.

Deterrence and the Death Penalty - National Research Council (The National Academies Press, 2012)
Many studies during the past few decades have sought to determine whether the death penalty has any deterrent effect on homicide rates. Researchers have reached widely varying, even contradictory, conclusions. Some studies have concluded that the threat of capital punishment deters murders, saving large numbers of lives; other studies have concluded that executions actually increase homicides; still others, that executions have no effect on murder rates. Commentary among researchers, advocates, and policymakers on the scientific validity of the findings has sometimes been acrimonious. Against this backdrop, the National Research Council report Deterrence and the Death Penalty assesses whether the available evidence provides a scientific basis for answering questions of if and how the death penalty affects homicide rates. This new report from the Committee on Law and Justice concludes that research to date on the effect of capital punishment on homicide rates is not useful in determining whether the death penalty increases, decreases, or has no effect on these rates. The key question is whether capital punishment is less or more effective as a deterrent than alternative punishments, such as a life sentence without the possibility of parole. Yet none of the research that has been done accounted for the possible effect of noncapital punishments on homicide rates. The report recommends new avenues of research that may provide broader insight into any deterrent effects from both capital and noncapital punishments.

Guidebook for Measuring Performance of Automated People Mover Systems at Airports - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine
TRB2019s Airport Cooperative Research Program (ACRP) Report 37A: Guidebook for Measuring Performance of Automated People Mover Systems at Airports is designed to help measure the performance of automated people mover (APM) systems at airports.The guidebook identifies, defines, and demonstrates application of a broad range of performance measures encompassing service availability, safety, operations and maintenance expense, capacity utilization, user satisfaction, and reliability.The project that developed ACRP Report 37A developed the set of forms below that are designed to help periodically compile the necessary data for input into the overall performance measurement process.Form A: System and Service Descriptive CharacteristicsForm B: Airport APM Performance Measures Page 1 of 2Form B: Airport APM Performance Measures Page 2 of 2Passenger Satisfaction SurveyThe project also developed an interactive Excel model containing spreadsheets that can be used to help track and calculate system-wide performance and service characteristics.The set of forms and Excel model are only available electronically.ACRP Report 37A is a companion to ACRP Report 37: Guidebook for Planning and Implementing Automated People Mover Systems at Airports, which includes guidance for planning and developing APM systems at airports.In June 2012, TRB released ACRP Report 67: Airport Passenger Conveyance Systems Planning Guidebook that offers guidance on the planning and implementation of passenger conveyance systems at airports.Disclaimer: The software linked to from this page is offered as is, without warranty or promise of support of any kind either expressed or implied. Under no circumstance will the National Academy of Sciences or the Transportation Research Board (collectively 201cTRB\

Terrorism and the Electric Power Delivery System - National Research Council (The National Academies Press, 2012)
The electric power delivery system that carries electricity from large central generators to customers could be severely damaged by a small number of well-informed attackers. The system is inherently vulnerable because transmission lines may span hundreds of miles, and many key facilities are unguarded. This vulnerability is exacerbated by the fact that the power grid, most of which was originally designed to meet the needs of individual vertically integrated utilities, is being used to move power between regions to support the needs of competitive markets for power generation. Primarily because of ambiguities introduced as a result of recent restricting the of the industry and cost pressures from consumers and regulators, investment to strengthen and upgrade the grid has lagged, with the result that many parts of the bulk high-voltage system are heavily stressed. Electric systems are not designed to withstand or quickly recover from damage inflicted simultaneously on multiple components. Such an attack could be carried out by knowledgeable attackers with little risk of detection or interdiction. Further well-planned and coordinated attacks by terrorists could leave the electric power system in a large region of the country at least partially disabled for a very long time. Although there are many examples of terrorist and military attacks on power systems elsewhere in the world, at the time of this study international terrorists have shown limited interest in attacking the U.S. power grid. However, that should not be a basis for complacency. Because all parts of the economy, as well as human health and welfare, depend on electricity, the results could be devastating. Terrorism and the Electric Power Delivery System focuses on measures that could make the power delivery system less vulnerable to attacks, restore power faster after an attack, and make critical services less vulnerable while the delivery of conventional electric power has been disrupted.

Perspectives on the Future of the Sociology of Aging - National Research Council (The National Academies Press, 2012)
The population of the United States is growing inexorably older. With birth rates historically low and life expectancy continuing to rise, the age distribution of the population in the United States is growing steadily older. This demographic shift is occurring at a time of major economic and social changes, which have important implications for the growing elderly population. Other changes, such as the move away from defined-benefit toward defined-contribution retirement plans, changes in some corporate and municipal pension plans as a result of market pressures, and the 2008 financial crisis precipitated by the crash of the housing market, all have economic implications for older people. They are also likely to make it more difficult for certain groups of future retirees to find their retirements at the level that they had planned and would like. To deal effectively with the challenges created by population aging, it is vital to first understand these demographic, economic, and social changes and, to the extent possible, their causes, consequences, and implications. Sociology offers a knowledge base, a number of useful analytic approaches and tools, and unique theoretical perspectives that can be important aids to this task. The Panel on New Directions in Social Demography, Social Epidemiology, and the Sociology of Aging was established in August 2010 under the auspices of the Committee on Population of the National Research Council to prepare a report that evaluates the recent contributions of social demography, social epidemiology, and sociology to the study of aging and seeks to identify promising new research in these fields. Perspectives on the Future of the Sociology of Aging provides candid and critical comments that will assist the institution in making the final published volume as sound as possible and to ensure that the volume meets institutional standards for objectivity, evidence, and responsiveness to the study charge.

Improving Measurement of Productivity in Higher Education - National Research Council (The National Academies Press, 2012)
Higher education is a linchpin of the American economy and society: teaching and research at colleges and universities contribute significantly to the nation's economic activity, both directly and through their impact on future growth; federal and state governments support teaching and research with billions of taxpayers' dollars; and individuals, communities, and the nation gain from the learning and innovation that occur in higher education. In the current environment of increasing tuition and shrinking public funds, a sense of urgency has emerged to better track the performance of colleges and universities in the hope that their costs can be contained without compromising quality or accessibility. Improving Measurement of Productivity in Higher Education presents an analytically well-defined concept of productivity in higher education and recommends empirically valid and operationally practical guidelines for measuring it. In addition to its obvious policy and research value, improved measures of productivity may generate insights that potentially lead to enhanced departmental, institutional, or system educational processes. Improving Measurement of Productivity in Higher Education constructs valid productivity measures to supplement the body of information used to guide resource allocation decisions at the system, state, and national levels and to assist policymakers who must assess investments in higher education against other compelling demands on scarce resources. By portraying the productive process in detail, this report will allow stakeholders to better understand the complexities of2014and potential approaches to2014measuring institution, system and national-level performance in higher education.

Assessment of Planetary Protection Requirements for Spacecraft Missions to Icy Solar System Bodies - National Research Council (The National Academies Press, 2012)
NASA's exploration of planets and satellites during the past 50 years has led to the discovery of traces of water ice throughout the solar system and prospects for large liquid water reservoirs beneath the frozen ICE shells of multiple satellites of the giant planets of the outer solar system. During the coming decades, NASA and other space agencies will send flybys, orbiters, subsurface probes, and, possibly, landers to these distant worlds in order to explore their geologic and chemical context. Because of their potential to harbor alien life, NASA will select missions that target the most habitable outer solar system objects. This strategy poses formidable challenges for mission planners who must balance the opportunity for exploration with the risk of contamination by Earth's microbes, which could confuse the interpretation of data obtained from these objects. The 2000 NRC report Preventing the Forward Contamination of Europa provided a criterion that was adopted with prior recommendations from the Committee on Space Research of the International Council for Science. This current NRC report revisits and extends the findings and recommendations of the 2000 Europa report in light of recent advances in planetary and life sciences and, among other tasks, assesses the risk of contamination of icy bodies in the solar system.

Living Well with Chronic Illness: A Call for Public Health Action - Institute of Medicine (The National Academies Press, 2012)
In the United States, chronic diseases currently account for 70 percent of all deaths, and close to 48 million Americans report a disability related to a chronic condition. Today, about one in four Americans have multiple diseases and the prevalence and burden of chronic disease in the elderly and racial\/ethnic minorities are notably disproportionate. Chronic disease has now emerged as a major public health problem and it threatens not only population health, but our social and economic welfare. Living Well with Chronic Disease identifies the population-based public health actions that can help reduce disability and improve functioning and quality of life among individuals who are at risk of developing a chronic disease and those with one or more diseases. The book recommends that all major federally funded programmatic and research initiatives in health include an evaluation on health-related quality of life and functional status. Also, the book recommends increasing support for implementation research on how to disseminate effective longterm lifestyle interventions in community-based settings that improve living well with chronic disease. Living Well with Chronic Disease uses three frameworks and considers diseases such as heart disease and stroke, diabetes, depression, and respiratory problems. The book's recommendations will inform policy makers concerned with health reform in public- and private-sectors and also managers of communitybased and public-health intervention programs, private and public research funders, and patients living with one or more chronic conditions.

Thinking Evolutionarily: Evolution Education Across the Life Sciences: Summary of a Convocation - National Research Council (The National Academies Press, 2012)
Evolution is the central unifying theme of biology. Yet today, more than a century and a half after Charles Darwin proposed the idea of evolution through natural selection, the topic is often relegated to a handful of chapters in textbooks and a few class sessions in introductory biology courses, if covered at all. In recent years, a movement has been gaining momentum that is aimed at radically changing this situation. On October 25-26, 2011, the Board on Life Sciences of the National Research Council and the National Academy of Sciences held a national convocation in Washington, DC, to explore the many issues associated with teaching evolution across the curriculum. Thinking Evolutionarily: Evolution Education Across the Life Sciences: Summary of a Convocation summarizes the goals, presentations, and discussions of the convocation. The goals were to articulate issues, showcase resources that are currently available or under development, and begin to develop a strategic plan for engaging all of the sectors represented at the convocation in future work to make evolution a central focus of all courses in the life sciences, and especially into introductory biology courses at the college and high school levels, though participants also discussed learning in earlier grades and life-long learning. Thinking Evolutionarily: Evolution Education Across the Life Sciences: Summary of a Convocation covers the broader issues associated with learning about the nature, processes, and limits of science, since understanding evolutionary science requires a more general appreciation of how science works. This report explains the major themes that recurred throughout the convocation, including the structure and content of curricula, the processes of teaching and learning about evolution, the tensions that can arise in the classroom, and the target audiences for evolution education.